Detection of Heavy Metal-Resistance Gene in Bacteria Isolated from Clinical and Environmental Sources Using Polymerase Chain Reaction (PCR) - Danny Sendolo; Glory Baysah; Cajethan Onyebuchi Ezeamagu (Adventist University of Africa, 2022)
Background: Global proliferation of the pharmaceutical industry in response to devastating health challenges has led to several ecological and environmental problems. Heavy metal contamination is one of the most dangerous factors that affect ecosystems and human health. This study aimed to detect the presence of heavy-metal resistance genes in clinical and environmental sources using polymerase chain reaction (PCR). Method: This study employed an experimental design. The samples included 40 clinical isolates (blood, urine, throat, wound, and sputum) and 40 environmental isolates (pharmaceutical effluents).The isolates were collected and subcultured in nutrient broth for analysis. Results: The result shows that heavy metal-resistant genes were not detected in the clinical isolates whereas 65% and 60% of the environmental isolates harbored silver (Ag) and arsenic (As) respectively. However, the clinical isolates in this study showed higher rates of resistance than the environmental isolates did. This may be due to the frequent use of broad-spectrum antibiotics during clinical sessions, leading to the development of antibiotic-resistant strains. Conclusion: Heavy metal-resistant genes are present in bacteria in the environment and may cause severe health issues (drug resistance) when these genes are transmitted to pathogenic organisms that affect humans and animals. The association between bacterial drug resistance and heavy metal acquisition may greatly influence treatment outcomes in the event of infection. Therefore, control measures should be implemented to reduce the dissemination of these metals in the environment.